Seizure As A Coercive Measure In A Comparison Of Criminal Procedural Law Between Indonesia And France - Salwa Aulia; Wevy Efticha Sary (University Of Bengkulu Law Journal, 2025)
Seizure is a form of coercive measure in criminal procedure law that inherently restricts constitutional rights, particularly the right to property and protection against arbitrary actions by law enforcement officials. Changes to criminal procedure law regulations in Indonesia through the New Criminal Procedure Code mark a fundamental reform of the investigation mechanism, including regulations on seizure. However, these normative reforms need to be critically examined to assess the extent to which the new regulations are able to guarantee due process of law and prevent abuse of authority. This article aims to analyze the provisions on seizure in the New Indonesian Criminal Procedure Code by comparing them with the seizure system in the French Code de procédure pénale as a representation of an established civil law system. This study uses a normative juridical method with a legislative, conceptual, and comparative legal approach. The results show that the New Criminal Procedure Code has strengthened the normative basis for seizure by confirming the objectives, objects, and procedures for seizure, but still leaves broad discretion to investigators. In contrast, French criminal procedure law places strong judicial control through a mechanism of judicial authorization and procedural guarantees for suspects and third parties. This comparison emphasizes the importance of strengthening judicial oversight and limiting the authority of investigators in the seizure system in Indonesia. This article contributes by formulating normative implications and offering a reconstruction of seizure regulations in the New Criminal Procedure Code that is oriented towards the protection of human rights, legal certainty, and the principle of proportionality in criminal procedure law.